Disturbed Laminar Blood Flow Causes Impaired Fibrinolysis and Endothelial Fibrin Deposition In Vivo - Glise, Lars; Larsson, Pia; Jern, Sverker; Borén, Jan; Levin, Malin; Ny, Tor; Fogelstrand, Per; Bergh, Niklas (Thrombosis and Haemostasis, 2019)
Endothelial expression of tissue-type plasminogen activator (t-PA) is crucial for maintaining an adequate endogenous fibrinolysis. It is unknown how endothelial t-PA expression and fibrinolysis are affected by blood flow in vivo. In this study, we investigated the impact of different blood flow profiles on endothelial t-PA expression and fibrinolysis in the arterial vasculature. Induction of disturbed laminar blood flow (D-flow) in the mouse carotid artery potently reduced endothelial t-PA messenger ribonucleic acid and protein expression, and caused fibrin deposition. En face immunohistochemistry demonstrated that arterial areas naturally exposed to D-flow had markedly lower endothelial t-PA levels than areas with sustained laminar blood flow (S-flow), and displayed pronounced fibrin deposition despite an intact endothelium. In t-PA and plasminogen-deficient mice, fibrin deposition did not extend into S-flow areas, indicating that areas of D-flow and S-flow differ, not only in fibrinolytic capacity, but also in coagulation. Furthermore, plasminogen accumulation was found at D-flow areas, and infusion of recombinant t-PA activated fibrinolysis and significantly reduced the fibrin deposits. In conclusion, D-flow potently impairs the fibrinolytic capacity and causes endothelial fibrin deposition in vivo. Our data also indicate that t-PA is the limiting factor for efficient fibrinolysis at the thrombosis-prone D-flow areas in the arterial vasculature.
Keywords: t-PA; artery; fluid shear; fibrinogen/fibrin